In Matfield Green, a Glimpse of a Viable Future - Paula Haas (Symphony in the Flint Hills, 2016)
In tiny Matfield Green the past is everywhere – a rusty horseshoe here, an abandoned stone step there, an old wooden shed melting to earth nearby.
Keywords: creativity; tallgrass prairie; ranch; artists; writers; education; printmaking; clients; bewildered; LOT 7A; GROUP A; LARGEST PLOTS OF LAND FOR SALE Robert Bubp; RURAL; Amanda Mactuba; VERDE; Anna Patricia Keller